2019
DOI: 10.1037/spq0000298
|View full text |Cite
|
Sign up to set email alerts
|

Latino parent involvement and associations with home literacy and oral reading fluency.

Abstract: Objective: Grounded in Hoover-Dempsey and Sandler's theoretical model of parents' motivations for involvement in their children's education, the aim of this study was to examine the associations between Latino parents' perceptions of involvement and the home literacy environment, as well as children's oral reading fluency (ORF). We further considered salient contextual factors (i.e., educational attainment, income status, and parent reading proficiency) that may impact parents' perceptions of involvement. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…These roles are believed to be effective in promoting children's reading development from the aspect of fluency (National Reading Panel, 2000;Henry, 2008;Pagan & Sénéchal, 2014;Sawyer et al, 2018;Brown et al, 2019;Zambrana et al, 2019;Yildirim et al, 2020), comprehension (National Reading Panel, 2000Gabl et al, 2007;Henry, 2008;Shany & Biemiller, 2009;Blanch et al, 2013;Pagan & Sénéchal, 2014;Brown et al, 2019;Yildirim et al, 2020) and interest (Cotter, 2012;Yeo, Ong & Ng, 2014;Levy, Hall & Preece, 2018;Choi, Kang & Sheo, 2020;Dobbs-Oates, Pentimonti, Justice and Kaderavek, 2015;Kathy, 2016). Traditionally, the roles as a motivator, tutor and facilitator in young learner's reading were given larger emphasis on the teachers in the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These roles are believed to be effective in promoting children's reading development from the aspect of fluency (National Reading Panel, 2000;Henry, 2008;Pagan & Sénéchal, 2014;Sawyer et al, 2018;Brown et al, 2019;Zambrana et al, 2019;Yildirim et al, 2020), comprehension (National Reading Panel, 2000Gabl et al, 2007;Henry, 2008;Shany & Biemiller, 2009;Blanch et al, 2013;Pagan & Sénéchal, 2014;Brown et al, 2019;Yildirim et al, 2020) and interest (Cotter, 2012;Yeo, Ong & Ng, 2014;Levy, Hall & Preece, 2018;Choi, Kang & Sheo, 2020;Dobbs-Oates, Pentimonti, Justice and Kaderavek, 2015;Kathy, 2016). Traditionally, the roles as a motivator, tutor and facilitator in young learner's reading were given larger emphasis on the teachers in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Zambrana et al (2019), the researchers concluded that the perception and role of parents are paramount in influencing young children's oral reading fluency and their account for contextual factors. Brown et al (2019) also yielded the same results as they realised that children's fluency and comprehension significantly increased after parent-child reading consistently for five months.…”
Section: Reading Problems Aided By Parents In Young Children's Readin...mentioning
confidence: 99%
“…Successful engagement models begin with creating an ecology where both generic and home literacy practices are valued, and families and teachers are positioned alongside one another as learners. Such an ecology would recenter families as powerful contributors to their child's education (Zambrana et al, 2019). Teachers would recognize and value the cultural literacy practices of bi/multilingual families, involve families in program creation, and design reading activities that are both meaningful and effective (Gaitan, 2012; Wood et al, 2018).…”
Section: Recentering the Ecology Of Family Literacy Partnershipsmentioning
confidence: 99%
“…Zambrana et al 9 suggested that Latino’s parents perceptions had much influence on the children home literacy but also their Oral Reading Skills, considering contextual salient factors (i.e., educational attainment, income status, and parent reading proficiency) as well.…”
Section: Introductionmentioning
confidence: 99%